APPLICATION OF RESTORATIVE JUSTICE IN EFFORTS TO RECOVER THE RIGHTS OF CHILD DEFENDERS WHO HAVE BEEN SENTENCED TO EXCEPTION - Rukmawati, Vita (JILPR Journal Indonesia Law and Policy Review, 2024)
Criminal justice legal regulations regarding child perpetrators of criminal acts of abuse have been implemented with diversion in the case of Decision Number 5/Pid.Sus-Anak/2022/PN JKT.PST so that child defendants are returned to their parents and Decision Number 24/Pid.Sus-Anak /2021/PN Jkt. Brt. by prosecutors and judges who do not apply diversion is indeed in accordance with the provisions of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System Article 7 (2). However, this is not in accordance with the principles of protection and prioritizing the best interests of the child's future and growth and development as stipulated in Law Number 35 of 2014 concerning Amendments to Law No. 23 of 2002 Articles 4 to Article 18 concerning Child Protection. The judge took diversion steps to uphold children's rights as regulated in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. Restoration of the rights of accused child perpetrators of abuse who have been sentenced to acquittal with restorative justice efforts (Case study of Decision Number 5/Pid.Sus-Anak/2022/PN JKT.PST and Decision Number 24/Pid.Sus-Anak/2021/PN Jkt. Brt is not appropriate where the judge does not carry out diversion which should be mandatory for criminal court cases involving children who are in conflict with the law to take diversion steps to carry out the diversion process so that children can resolve cases outside the court which is an embodiment of Article 59 of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection.